Are Political Parties Recapturing the Streets of Europe? - Endre Borbáth; Swen Hutter (Contention in Times of Crisis. Recession and Political Protest in Thirty European Countries, 2020)
Political mobilization in the electoral and protest arenas have long been studied as separate phenomena, following their own, independent dynamic. Parties and protests are rarely examined within the same framework, although the protest engagement of political parties is often assumed to be one of the main driving forces of the wave of protest in southern European countries, those most exposed to the economic crisis. The chapter provides the first large-scale study of protests sponsored by political parties across Europe before and after the Great Recession. It relies on a novel protest event dataset, collected by semi-automated content analysis of news agencies. The data cover protests in thirty countries, from 2000 to 2015. The results show the `crowding out' of political parties as the driving force of the protest wave in southern Europe. We find the highest share of party sponsored protest in eastern Europe, where unlike in north-western and southern Europe, right-wing and non-mainstream parties are also active in protest. In line with the overall findings of the book, our results confirm the distinctive dynamic of protest in the three European macro-regions and put the link between social movements and the new challenger parties in perspective.
Keywords: 300; political parties; protest politics; economic crisis; movement parties; civil society; electoral arena; protest arena; protest event analysis; automated content analysis; Europe